Metabolic Plasticity of Gilthead Seabream Under Different Stressors: Analysis of the Stress Responsive Hepatic Proteome and Gene Expression - Raposo de Magalhães, Cláudia; Schrama, Denise; Nakharuthai, Chatsirin; Boonanuntanasarn, Surintorn; Revets, Dominique; Planchon, Sébastien; Kuehn, Annette; Cerqueira, Marco; Carrilho, Raquel; Farinha, Ana Paula; Rodrigues, Pedro M. (Frontiers in Marine Science, 2021)
Hepatic metabolic adjustments are key adaptive mechanisms to stress in fish targeting at increasing energy availability for the animal to efficiently cope with a stressor. Teleosts exhibit a broad variety of these metabolic responses, depending on the species biology, individual experiences and the challenge’s characteristics. Nevertheless, the molecular response to a prolonged stress can be more heterogeneous and far more complex to interpret than that to an acute stress. A comparative proteomics analysis was employed to discover the set of liver proteins involved in the adaptive processes that tune the physiological response of Sparus aurata to different suboptimal rearing conditions and physical challenges. Three separated trials were established where fish were submitted to different conditions (overcrowding, net handling and hypoxia). The response at the transcript level of 13 genes was also assessed. Mass spectrometric analysis revealed 71 differential abundant proteins distributed among the trials. Prolonged exposure to stress seems to have induced widespread changes in amino acid, carbohydrate, and lipid metabolisms, antioxidant response and protein folding, sorting and degradation processes. Two genes corresponding to heat-shock proteins were found to be differently expressed in net handled fish. These results shed light on the dynamics and extent of this species’ metabolic reprogramming under different challenges, supporting future studies on stress markers’ discovery and fish welfare research.